Collagen VI microfibril structure reveals mechanism for molecular assembly and clustering of inherited pathogenic mutations - Alan R. F. Godwin; Mark H. Becker; Rana Dajani; Matthew Snee; Alan M. Roseman; Clair Baldock (Nature Communications)
Abstract Collagen VI links the cell surface to the extracellular matrix to provide mechanical strength to most mammalian tissues, and is linked to human diseases including muscular dystrophy, fibrosis, cardiovascular disease and osteoarthritis. Collagen VI assembles from heterotrimers of three different α-chains into microfibrils, but there are many gaps in our knowledge of the molecular assembly process. Here, we determine the structures of both heterotrimeric mini-collagen VI constructs and collagen VI microfibrils, from mammalian tissue, using cryogenic-electron microscopy. These structures reveal a cysteine-rich coiled coil region involved in trimerisation as well as microfibril assembly. Furthermore, our structures show that pathogenic mutations are located at interaction sites involved in different steps of collagen VI assembly, from the trimeric-coiled coil region that mediates heterotrimerisation, to clusters of mutations in the triple-helical region involved in microfibril formation. Our microfibril structure provides a template for understanding supramolecular assembly, and offers a platform for rationale design of therapeutics for collagen VI pathologies.